Digital Branding Adaptation For Indonesian Small Medium Enterprises Expansion Into Global Market - Siswanto, Riky Azharyandi (2023)
The function of branding in enhancing the competitiveness of Small Medium Enterprises in Indonesia continues to be a particular goal for numerous stakeholders. These efforts constantly encounter obstacles for providing direct branding services to SMEs since there is no aid available in the market. Meanwhile, the phenomenon of the digital world's development has an impact on how brands are established. While digital marketing continues to become an affordable approach for marketing, digital branding continues to increase in cost. On the other side, there are thousands of unemployed recent grads and graphic design students for providing direct branding services to SMEs. Between SMEs and inexperienced designers, there is enormous untapped potential. This is because the disparity between the financial capacities of SMEs and graphic designers discourages graphic artists from providing their services to SMEs. To meet the objectives of both parties, a system is required that streamlines the branding process, reduces branding costs, and improves the resulting branding's quality, demonstrating that this may either boon or a bane for SMEs seeking to increase their competitiveness through digital branding. A new ecosystem model is required that enables access to digital branding SME business owners that are capable of advancing their goals.